Between Technological Innovation and Pagan Tradition: The Representation of Lithuania in Contemporary German Travel Literature - Burov, Aleksej; Kotovičius, Tomas Vytautas (Literatūra, 2025)
This article explores Lithuania’s hetero-image as it is created in contemporary German travel literature. The scope of the research primarily covers three German travelogues which detail the authors’ experience during their travels in Lithuania: Drei Baltische Wege (Lucius von, 2011), Wo die Ostsee Westsee heißt (Bünz, 2018) and Gebrauchsanweisung für das Baltikum (Herre, 2014). A further source also contributes to the given analysis: The Strategy for the Presentation of Lithuania abroad 2020–2030, compiled by the Lithuanian government in 2020, and the brief communicative messages conveyed in the document, which revolve around several particulars of Lithuania’s image: economy, culture, history, science and geographic location. These messages mirror Lithuania’s auto image and present the main assessment categories chosen for analyzing the German travelogues. The article concludes that the four most widely covered aspects of economy, culture, history and science, on the one hand, convey an image of a country known for its technological advancement, cultural impact and historical significance. On the other hand, however, they portray an economically underdeveloped and politically unstable country with a generally disgruntled population. Lithuania’s geographic location is tied not to Eastern or Northern Europe, but rather to Central Europe.